Pedagogical conditions for the organization of work with vocationally oriented text in the process of teaching a foreign language - Irina A. Pushkareva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки, 2021)
The author of the paper attempts to develop a set of pedagogical conditions that contribute to the organization of effective work of students with a vocationally oriented text in the process of learning a foreign language in order to form common cultural and professional competencies.